Neck and Back Pain among Dentists in Erbil City - Kaifi Wali; Jawad Mikael; Twana Bakr (Erbil Dental Journal)
Background and objectives: Work-associated musculoskeletal disorders have become a common phenomenon and can happen over time as a result of exposing to workload repeatedly. Common regions that vulnerable to include Work-associated musculoskeletal disorders the neck and lower back. The objectives of the study were to assess the prevalence, causes, severity, and extent of lower back and neck pain among the dentists in Erbil city.